Resilience of ancestral lands culture in Kenya: A religious discourse - Mumo, Peter Mutuku (Ilorin journal of religious studies, 2021)
Africans in Africa and in the Diaspora have consistently insisted on being buried in their ancestral lands in Africa. Ancestral lands are associated with origin, identity, values, livelihood and culture. The significance of ancestral lands culture in Africa cannot be gainsaid. The article examines the resilience of ancestral lands in Kenyan society in particular and Africa in general. It is argued that although Kenya is amongst African countries most influenced by modern changes, especially by Christianity, western culture and Islam, belief in the sacredness of ancestral lands has persisted. The article is mainly based on library research and views of African scholars, including African Christian theologians. The article found out that despite the introduction of Islam and Christianity which together have adherence of over 90% of the Kenyan population, majority of Kenyans due to the influence of African Religion and culture still view ancestral lands as sacred and would like to be buried in their own ancestral lands, whether purchased or inherited. Some Kenyan Christian elites have diversified their beliefs and largely been influenced by modernity and secularization hence a few of them have opted for cremation or burial in public cemeteries, yet, the ancestral land culture is not about to die. It is concluded that in Kenya, like in some other African countries, the question of ancestral lands is still significant, as most Kenyans still occupy ancestral lands which are still viewed as sacred and indicative of the resilience of traditional African influence.